Detection of complex organic molecules in young starless core L1521E. Issue 4 (23rd April 2021) - Scibelli, Samantha; Shirley, Yancy; Vasyunin, Anton; Launhardt, Ralf
ABSTRACT: Determining the level of chemical complexity within dense starless and gravitationally bound pre-stellar cores is crucial for constructing chemical models, which subsequently constrain the initial chemical conditions of star formation. We have searched for complex organic molecules (COMs) in the young starless core L1521E, and report the first clear detection of dimethyl ether (CH3 OCH3 ), methyl formate (HCOOCH3 ), and vinyl cyanide (CH2 CHCN). Eight transitions of acetaldehyde (CH3 CHO) were also detected, five of which (A states) were used to determine an excitation temperature to then calculate column densities for the other oxygen-bearing COMs. If source size was not taken into account (i.e. if filling fraction was assumed to be one), column density was underestimated, and thus we stress the need for higher resolution mapping data. We calculated L1521E COM abundances and compared them to other stages of low-mass star formation, also finding similarities to other starless/pre-stellar cores, suggesting related chemical evolution. The scenario that assumes formation of COMs in gas-phase reactions between precursors formed on grains and then ejected to the cold gas via reactive desorption was tested and was unable to reproduce observed COM abundances, with the exception of CH3 CHO. These results suggest that COMs observed in cold gas are formed not by gas-phase reactions alone, but also through surface reactions on interstellar grains. Our observations present a new, unique challenge for existing theoretical astrochemical models.